The pig in the python: US decennial labor flows and economic opportunity, 1910–2040 - Steven Ruggles (Proceedings of the National Academy of Sciences, 2026)
This analysis revisits the relative cohort size hypothesis proposed by demographer Richard Easterlin in the 1960s. Easterlin argued that the economic and social prospects of a generation are influenced by the size of the cohort relative to adjacent cohorts. He hypothesized that relative cohort size affects wages, employment, marriage, and fertility decisions. The theory fits the data well for the period from 1940 to 1980 but fails in later decades. I present a more nuanced view of the impact of demographic factors on worker competition through the lens of a measure of decennial labor-force flows. This approach allows consideration of the effects of retirement, female labor-force participation, and immigration on labor-market competition. I calculate these flows for the period from 1910 to 2040 and propose an index of employment competition. The results show that trends in labor-market competition are consistent with wage trends of young workers since 1940. Projections to 2040 show that we are on the verge of a radical reshaping of labor markets in which new workers will be in extremely short supply.